Assessing the real-world safety of fenofibric acid for hyperlipidemia: results from WHO-VigiAccess and FAERS databases - Li, Yaxing; Wang, Yi; Zhang, Jidang; Zhang, Ruonan; Yao, Zhiwen; Chen, Xuepin; Xu, Xingli (Frontiers in Medicine, 2025)
BackgroundFenofibric acid is a small-molecule fibrate that functions as an agonist of peroxisome proliferator-activated receptor alpha (PPARα) and serves as an inhibitor of liver fatty acid-binding protein. It is primarily prescribed for the management of hyperlipidemia, including conditions such as hypercholesterolemia and hypertriglyceridemia. As a lipid-lowering agent, a comprehensive understanding of the real-world safety profile of fenofibric acid is essential to ensure its safe and effective use in clinical practice.MethodsThis study utilizes four disproportionality analysis methods to investigate adverse event (AE) reports related to fenofibric acid in the WHO VigiAccess and FDA Adverse Event Reporting System (FAERS) databases, thereby providing robust scientific evidence for evaluating the real-world safety of fenofibric acid. Additionally, the study applies the Weibull distribution to estimate the timing of adverse event occurrences. The study investigates the relationship between adverse event reports and gender via gender-stratified analysis.ResultsThis study retrieved 323 adverse event reports from WHO VigiAccess and 1,970 reports from FAERS. Drug-related signals were detected in 23 and 26 System Organ Class levels in the WHO VigiAccess and FAERS datasets, respectively. The study results confirmed known adverse reactions of fenofibric acid, including renal impairment, hepatobiliary toxicity, pancreatitis, and allergic reactions. Additionally, several potential adverse effects were identified, including gout, hypoglycemia, prothrombin time prolonged, photosensitivity reactions, rash, blood creatine and creatinine increased, blood creatine phosphokinase increased, myalgia, muscle fatigue, pain in extremity, joint pain and headache. The findings further underscore the importance of monitoring adverse events during the first 3 months of fenofibric acid use. The findings also highlight that closer attention to adverse events among female patients may have important clinical implications.ConclusionIn addition to the known adverse reactions, this study has identified numerous potential adverse drug reactions associated with fenofibric acid. Although these findings require further validation through subsequent clinical trials, they provide valuable safety information for clinicians to consider when evaluating adverse effects in patients treated with fenofibric acid.